2017
DOI: 10.1007/s10616-017-0127-y
|View full text |Cite
|
Sign up to set email alerts
|

Sufentanil protects the rat myocardium against ischemia–reperfusion injury via activation of the ERK1/2 pathway

Abstract: Sufentanil, a lipophilic opioid, is the most frequently used clinical drug for ischemic heart disease. The effects of sufentanil on MAPK signaling in ischemic heart disease were explored. The effects of sufentanil on ischemia-reperfusion (IR)-induced myocardial injury in a rat model were examined. The serum levels of CK, LDH, MDA and SOD, and the activities of Na-K-ATPase and Ca-Mg-ATPase were measured. The levels of total and phosphorylated ERK1/2, JNK, and p38 were measured by western blotting in the heart, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Wu et al [ 15 ] demonstrated that sufentanil postconditioning could protect the myocardium from I/R by activating PI3K/Akt-GSK-3 β pathway and regulating BCL2-Associated X (Bax) and Bcl-2 expression. Tao and Nuo [ 16 ] found that sufentanil could protect the rat myocardium from I/R injury by activating the ERK1/2 pathway. However, there are not many reports on the involvement of ER stress in the process that sufentanil protects the rat myocardium from IR injury.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [ 15 ] demonstrated that sufentanil postconditioning could protect the myocardium from I/R by activating PI3K/Akt-GSK-3 β pathway and regulating BCL2-Associated X (Bax) and Bcl-2 expression. Tao and Nuo [ 16 ] found that sufentanil could protect the rat myocardium from I/R injury by activating the ERK1/2 pathway. However, there are not many reports on the involvement of ER stress in the process that sufentanil protects the rat myocardium from IR injury.…”
Section: Introductionmentioning
confidence: 99%
“…During the reperfusion period, the generation of ROS leads to multiple cellular damage, which is an important risk factor in the occurrence and development of cardiovascular ischemic diseases [19,20]. It has been well reported that sufentanil can decrease the content of MDA, which is the end product of lipid peroxidation and a biomarker for oxidative stress [7,21]. SOD serves as an important anti-oxidase, which participates in protecting against oxidative stress during myocardial I/R injury [22,23].…”
Section: Sufentanil Relieved Oxidative Stress Induced By Ogd/r In H9cmentioning
confidence: 99%
“…The clinical drug that is commonly used for ischemic heart disease is sufentanil, a lipophilic opioid. It has been well reported that sufentanil treatment is able to protect the rat myocardium from I/R injury [7]. In a rabbit model of myocardial I/R, intrathecal sufentanil exhibited a cardioprotective effect [8].…”
Section: Introductionmentioning
confidence: 98%
“… 8 In addition, SUF has also been found to alleviate myocardial ischemia-reperfusion injury by activating the ERK1/2 signaling pathway or miR-125a/DRAM2 axis. 10 , 11 A clinical study also shows that SUF can alleviate ischemia-reperfusion injury in patients with coronary heart disease. 12 Therefore, we speculated that SUF may have a therapeutic effect on ischemia-reperfusion disease.…”
Section: Introductionmentioning
confidence: 99%